Enhancing antenatal knowledge through gamification: Evaluating the pregnant mother game application, a level 3 research and development - Lisnawati Lisnawati; Rani Widiyanti; Pepi Hapitria; Dena Latif Setiawan (Golestan University of Medical Sciences, 2024)
Background: The Pregnant Mother Game application is designed to enhance midwifery services, particularly for online antenatal classes. It is developed by experts in learning media and presented in a game format. The objectives of this research are to develop apps for antenatal classes and to assess how well these applications increase mothers' knowledge. Methods: It is a level 3 Research and Development, which is developing and refining products. The participants were selected using a purposive sampling technique. Limited trials of the application, which is downloadable on Android devices, were carried out with 10 first-time pregnant women in Cirebon City, Indonesia. Data collection tools included a questionnaire for experts and mothers. Data were analyzed using IBM SPSS Statistics 16, with univariate analysis employing a frequency distribution and bivariate analysis utilizing the Wilcoxon test. The significance level was set at 0.05, with a 95% confidence interval. Results: The material experts' qualifying test yielded a score of 85% (very decent), and the media members' score was 84.4% (very decent). There was a 50% increase in the mean knowledge value. The pretest score ranged between 10 and 25, while the posttest score ranged between 25 and 29. The use of the application was correlated with increased knowledge score, and the correlation coefficient was significant at 0.05. Conclusion: The program can be used as an effective technology medium for conducting online classes for mothers. The mothers' knowledge significantly improved after taking online classes with the application.